Correlation and Path Analysis Maize Hybrid Yield - Slamet Bambang Priyanto; Oky Dwi Prayitno; Roy Efendi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
The yield was a complex quantitative character. It was due to many other characters being related to yield. This study aimed to determine the correlation between agronomic characters in maize and the characters that affect the yield of hybrid maize. This experiment was conducted at the Bajeng IP2TP, Indonesian Cereal Research Institute, Gowa, South Sulawesi from March to June 2022. The treatments consisted of ten hybrid maize genotypes. The treatments were arranged in a Randomized Complete Block Design (RCBD) with three replications. The variables observed were the agronomic component and yield component. Pearson's correlation was used to determine the relationship between characters, and the characters that affected the grain yield were determined by path analysis. The results showed the characters leaf length, leaf width, harvested plant number, harvested ear number, harvested ear weight, shelling percentage, ear length, ear diameter, kernel number per row and 1000 grains weight have a significant correlation to yield. Characters that affected to maize yields were harvested ear weight, shelling percentage and grain moisture.